Nipah Virus Antibodies in Bats, the Philippines, 2013–2022 - Kaku, Yoshihiro; Watanabe, Shumpei; Masangkay, Joseph S.; Alviola, Phillip; Taniguchi, Satoshi; Cosico, Edison; Une, Yumi; Recuenco, Frances C.; Sugimoto, Satoko; Kato, Kentaro; Kyuwa, Shigeru; General, David Emmanuel M.; et al. (Emerging infectious diseases, 2025)
In 2014, an outbreak of zoonotic Nipah virus (NiV) occurred on Mindanao Island, the Philippines. We investigated the prevalence of NiV in Philippine bats. Because neutralizing antibodies were detected in insectivorous bats on Siargao Island, public health officials should consider that the distribution range of NiV is not limited to Mindanao Island.